P54 Which Secondary Care Asthma Patients Are Most Likely To Overestimate Their Control? A Cross-sectional Study. (10th November 2014) - Patel, L; Blakey, J; Mortimer, K
Abstract : Introduction: Asthma is a global health issue affecting 300 million people worldwide; with increasing prevalence and morbidity and preventable mortality. Despite advances in management the number of asthma related deaths has not improved. Asthma is a heterogeneous condition, with a variety of clusters of clinical presentations and courses, objective measures and treatment responses. A common feature of asthma is the under-reporting of poor symptom control by patients and under-recognition by clinicians. Poor asthma control in the preceding 12-months prior to admission has been linked to asthma related deaths. The significance of measuring asthma control independently from asthma severity has been demonstrated. However, considerable differences in perceived and actual control are apparent. There is a need to identify patient groups at risk of under-reporting symptoms and not recognising poor control. Aim: To establish which patient features are associated with overestimation of disease control. Setting: Secondary care consultant led asthma clinic. Population: 108 patients recruited over 10 weeks. Measures: Objective measures of disease severity were mapped against perceived symptom control using the Asthma Control Test; age, gender, co-morbidities, medications, induced sputum, lung function, IgE, blood eosinophil, histamine challenge test, exhaled nitric oxide, ECG CXR, smoking status and BMI. Analysis: Significant associations between patient groups and perceptions of symptom control are described. Results: 61 (56.6%) of patients had difficult asthma according to BTS guidance. 95 (88.0%) had poorly controlled asthma, with 70 (64.8%) of these perceiving adequate control of symptoms. All patients with good perceived and actual control of symptoms; 13 (12.0%), had never smoked. 85.5% of patients who did not recognise their symptoms prevalence were overweight, obese or morbidly obese. All patients with raised IgE or blood eosinophillia had poorly controlled asthma; though 58.6% of this group perceived good control. Conclusion: This single centre cross-sectional study suggests smokers, overweight patients and those with inflammation predominant asthma are most likely to under-report severity. These findings are in keeping with the cluster analyses of Haldar and Moore. Further work is required to follow-up these patients to establish if poor perception of symptoms changes over time, or is associated with future asthma attack frequency.